GCF, HARALIK HÁM RMS SÚWRET KONTRASTIN ETALONSIZ BAHALAW KÓRSETKISHLERI - Mamatov, N.S.; Jalelova, M.M.; Tojiboeva, Sh.X. (SCIENCE and SOCIETY, 2023)
In this article, methods of evaluating the contrast, which is one of the parameters that determine the quality of the image, are considered without an objective standard. Benchmark-free methods are important in automating the process of image processing, because in practical problems there will be no benchmark image. GCF (global contrast factor), Haralik contrast and RMS (root mean square) criteria were selected based on experiments among these non-standard methods and were confirmed to give good results compared to other criteria.